(untitled) (Vietnam Journal of Community Medicine, 2021)
Quality of life is a widely used concept to measure the results of treatment of patients in general and patients with genital warts in particular. To provide data on the quality of life of warts patients treated at the National Hospital of Dermatology, as a basis for improving the quality of treatment, we conducted this study to: Describe the quality of life. Survival of patients with warts treated at the National Hospital of Dermatology. This is a cross-sectional descriptive study. Information was collected through interviews with 210 patients with warts treated at the National Hospital of Dermatology (December 6, 2020) using the QE-5D-5L quality of life measurement tool kit. Research results show that the quality of life is quite and good accounted for 57.6% with a quality of life score of 0.9910 ± 0.058, an average quality of life is quite good at 36.2% with a quality of life score of 0.729 ± 0.048, mean quality of life is 2.9% with quality of life score of 0.533 ± 0.043, patients with poor quality of life account for 3.3% of quality of life, which is 0.288 ± 0.101.